A Guide to Evaluation of Value for Money in UK Public Services - King, Julian; Hurrell, Alex (Verian, 2024)
When assessing value for money (VfM), there are sound arguments for co mbining insights from economics and evaluation. Drawing on the complem entary strengths of both disciplines supports comprehensive assessment of policies and programmes’ VfM. In this Guide we introduce an interd isciplinary approach, Value for Investment, that integrates methods an d tools from both disciplines, and which has gained traction worldwide . Among the concepts and methods of evaluation that economics brings t o this interdisciplinary mix is cost-benefit analysis (CBA), which eva luates whether an intervention creates more value for society than it consumes. CBA is vital in the UK policy context, acting as a key tool for evaluating public policies, programmes, and projects as set out in the Green Book, HM Government’s central guide for appraisal and evalu ation, and the Magenta Book which focuses on evaluation methodologies and practices across the whole policy cycle. Together, the Green Book and Magenta Book form a robust framework for evidence-based policymaki ng, ensuring CBA informs sound decision-making and evaluates implement ed policies’ impacts. Within this policy context, value for money (VfM ) is often framed as an objective or question within an evaluation and is commonly equated with CBA. However, we argue that while CBA contri butes important evidence, it may be insufficient. The approach set out in this Guide includes economic analysis while integrating multiple v alues (social, economic, environmental, and cultural) and diverse evid ence sources (quantitative and qualitative) for a more comprehensive V fM assessment, drawing on the strengths of CBA without limiting the ev aluation to economic methods and metrics alone. The Value for Investme nt approach uses mixed methods (integrating quantitative and qualitati ve evidence), employs evaluative reasoning (interpreting evidence thro ugh the lens of explicit criteria and standards – improving transparen cy in the rationale for evaluative judgements), and is participatory ( involving stakeholders in co-design and analysis). It is designed to b e intuitive and practical to use by following a logical sequence of st eps. The Value for Investment approach was developed through doctoral research (King, 2017; 2019) and refined through real-world VfM evaluat ions in diverse contexts. Leading examples of its application are publ ished in Assessing Value for Money – the Oxford Policy Management Appr oach (King, Wate, Namukasa, Hurrell, Hansford, Ward, & Faramarzifar, 2 023), and Value for Investment – Application and Insights (King, Crock et, & Field, 2023). This Guide is designed to complement existing VfI guidance by focusing on the interface between CBA and other evaluation methods to provide sound answers to VfM questions in the context of U K public policy.